A Ordem Nymphaeales no Estado da Bahia, Brasil - Lima, Carla Teixeira de (2011)
The State of Bahia occupies a large area which includes diverse ecosystems, which are related to three major biomas: Atlantic Forest, Caatinga and Cerrado. Such environmental diversity is reflected in the enormous level of biodiversity, as shown by the recently published “Catálogo das Plantas e Fungos”, which listed Bahia as the State with the second greatest number of Angiosperm species. Eastern Bahia is largely occupied by Mata Atlantica (or was, until the early 20th century, when much forest destruction occurred), while the western part of Bahia is mostly cerrado. More than half the State, in the more central part, is occupied by the Semi-arid Zone, characterized by irregular rainfall and long periods of drought. Although, during the rainy season, the area supports superficial, mostly temporary bodies of water, there are rarely also a few, which are longer-lived or permanent. In these pools or lakes, one can find macrophytic communities of great beauty but poorly studied. Among other families are found Cabombaceae and Nymphaeaceae, together with Hydatellaceae, also in the Nymphaeales. The Nymphaeales are a monophyletic order, representing one of the most ancient lineages within the Flowering Plants. Historically, Cabombaceae and Nymphaeaceae have been treated as one or two families. Molecular studies, using various genomic regions, both nuclear and mitochondrial, together with morphological analyses, support the recognition of two families, each monophyletic and with independent lineages, as represented in APGIII. This delimitation is followed in the present study. Nymphaeales are characterized by their aquatic habit, with simple, submerged, floating or emergent leaves and with showy, floating or emergent flowers. However, while the flowers of Cabombaceae possess three carpels, those of Nymphaeaceae are multicarpellate. Both families are widely distributed, occupying rivers, lakes, fresh-water lagoons and other similar habitats. Cabombaceae includes two genera of which only Cabomba occurs in Brazil, with four species in Bahia: Cabomba aquatica Aubl., C. caroliniana A. Gray var. caroliniana, C. furcata Schult. & Schult.f. and C. haynesii Wiersema. Nymphaeaceae contains two genera in Brazil, Nymphaea and Victoria, with six species in Brazil: Nymphaea amazonum Mart. & Zucc subsp. amazonum; N. caerulea Savigny; N. lasiophylla Mart. & Zucc.; N. lingulata Wiersema; N. pulchella DC. and N. rudgeana G. Mey. Based on extensive field-work in all regions of Bahia and analysis of material from a number of herbaria, all material was determined, species descriptions, illustrations and keys were made, and these were prepared as treatments of the two families as a contribution to the Flora of Bahia Project (Chapters 3 and 4). More detailed studies are also presented of certain aspects of the morphology of the two families and Floral Biology of species of Cabomba. (Chapters 1 and 2).